Toward a personalized closed-loop stimulation of the visual cortex: Advances and challenges - Grani, Fabrizio; Soto-Sánchez, Cristina; Fimia, Antonio; Fernández, Eduardo (Frontiers in Cellular Neuroscience, 2022)
Current cortical visual prosthesis approaches are primarily unidirectional and do not consider the feed-back circuits that exist in just about every part of the nervous system. Herein, we provide a brief overview of some recent developments for better controlling brain stimulation and present preliminary human data indicating that closed-loop strategies could considerably enhance the effectiveness, safety, and long-term stability of visual cortex stimulation. We propose that the development of improved closed-loop strategies may help to enhance our capacity to communicate with the brain.